Analisis Tata Kelola E-Government Menggunakan Framework COBIT 5 pada Diskominfo Sidoarjo - Niswatin Nadifah Maghfiroh; Fedora Helau Nana; Yusuf Amrozi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The Sidoarjo Regency Communication and Information Office is a government agency that has the task of carrying out its authority in the field of communication and informatics. This study aims to analyze e-government governance using the COBIT 5 framework to determine the maturity level value. Applying descriptive qualitative research with case study methods and research data in the form of primary and secondary data derived from literature and document studies along with the results of interviews with informants from relevant agencies and several communities involved in the use of e-government. Based on the results obtained, the average value for the BAI01 domain (Managing Programs and Projects) is 1.36 and reaches maturity level 1 (Initial level) while the APO12 (Risk Management) domain is 2.33, BAI05 (Managing Organizational Change Activation) 2.57, DSS02 ( Managing Service Requests and Incidents) 2.57, and DSS04 (managing sustainability) 2.75 which means reaching maturity level 2 (Repeatable level). Thus, Diskominfo Sidoarjo can improve organizational performance by responding to and articulating the risks that occur, managing stakeholder compliance, monitoring and controlling program results, planning and iterating projects, instilling new approaches to the organization, and conducting continuous training to optimize human resources.